A person-centred observational tool: devising the Workplace Culture Critical Analysis Tool®. (12th February 2020) - Wilson, Val; Dewing, Jan; Cardiff, Shaun; Mekki, Tone Elin; Øye, Christine; McCance, Tanya
No abstract available